2023
DOI: 10.1101/gr.277481.122
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese indicine pangenome reveals a wealth of novel structural variants introgressed from otherBosspecies

Xuelei Dai,
Peipei Bian,
Dexiang Hu
et al.

Abstract: Chinese indicine cattle harbor a much higher genetic diversity compared with other domestic cattle, but their genome architecture remains uninvestigated. Using PacBio HiFi sequencing data from 10 Chinese indicine cattle across southern China, we assembled 20 high-quality partially phased genomes and integrated them into a multiassembly graph containing 148.5 Mb (5.6%) of novel sequence. We identified 156,009 high-confidence nonredundant structural variants (SVs) and 206 SV hotspots spanning ∼195 Mb of gene-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…We compared domestic sheep/goat populations with their congeneric wild relatives to search for potentially introgressed SVs using a method for SV-based introgression analysis in previous studies [ 239 , 240 ]. For each domesticated population (88 native sheep populations and 14 native goat populations) and each wild species (7 wild sheep species and 6 wild goat species), we used VCFtools v.0.1.16 [ 203 ] to calculate the allele frequency of each SV with the option “-freq.” The candidate introgressed SVs from wild species to domestic populations were identified based on the following criteria: (i) SV was specific to one domestic population and fixed in any wild species (allele frequency = 1), but was absent from any other domestic populations (allele frequency = 0); (ii) allele frequency of SV should be zero in bighorn sheep ( Ovis canadensis ) for sheep [ 11 ] and Siberian Ibex ( Capra sibirica ) for goats [ 241 ], so as to exclude the candidate introgressed SVs due to common ancestor; (iii) each domestic population included in the introgression analyses should have at least 2 samples and each introgressed population should have more than 2 candidate introgressed SVs, so as to exclude the potential influence of genetic drift on the results.…”
Section: Methodsmentioning
confidence: 99%
“…We compared domestic sheep/goat populations with their congeneric wild relatives to search for potentially introgressed SVs using a method for SV-based introgression analysis in previous studies [ 239 , 240 ]. For each domesticated population (88 native sheep populations and 14 native goat populations) and each wild species (7 wild sheep species and 6 wild goat species), we used VCFtools v.0.1.16 [ 203 ] to calculate the allele frequency of each SV with the option “-freq.” The candidate introgressed SVs from wild species to domestic populations were identified based on the following criteria: (i) SV was specific to one domestic population and fixed in any wild species (allele frequency = 1), but was absent from any other domestic populations (allele frequency = 0); (ii) allele frequency of SV should be zero in bighorn sheep ( Ovis canadensis ) for sheep [ 11 ] and Siberian Ibex ( Capra sibirica ) for goats [ 241 ], so as to exclude the candidate introgressed SVs due to common ancestor; (iii) each domestic population included in the introgression analyses should have at least 2 samples and each introgressed population should have more than 2 candidate introgressed SVs, so as to exclude the potential influence of genetic drift on the results.…”
Section: Methodsmentioning
confidence: 99%
“…Following the advent of NGS, the de novo sequencing of livestock species became feasible, typically by constructing a reference genome based on a representative breed [13]. TGS technologies demonstrate remarkable advantages and enormous potential in genome assembly research, and they are widely applied in various animals, such as cattle [14,15], gayals [16], yaks [17,18], buffalos [19,20], sheep [21,22], goats [23,24], pigs [25,26], chickens [27,28], ducks [29], and geese [30] (Table 1).…”
Section: Progress In Genome Assembly Using Tgs In Livestockmentioning
confidence: 99%
“…In cattle, researchers constructed a graphical pan-genome for 10 southern Chinese yellow cattle breeds, utilizing the high accuracy and continuity advantages of local directional haplotype genomes. They clarified five gene infiltration events from different wild cattle species in the population history of southern Chinese yellow cattle [15]. Liu et al built a graphical pan-genome for yak and cattle species, discovering that nearly 90% of the domestic yak genome contains genes that have infiltrated from yellow cattle.…”
Section: Understanding the Genetic Mechanisms Of Traits In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic structural analysis detected novel structural variations, including deletion, duplication, and inversion variants, which provided genetic information about loci in the bovine genome that may underlie the phenotypic diversity. Dai et al [42] constructed a Chinese indicine pangenome across southern China, and identified 148.5 Mb of novel sequence. The interspecies introgression landscape revealed the unique genetic diversity and functional variation among the indicine cattle populations.…”
Section: Bovine Pangenome Studiesmentioning
confidence: 99%